Investigating Writing Instrument and Descriptive Paragraph Web-blog based - Eva Hartiningsih; M. Fadhly Farhy Abbas (ELT-Lectura, 2022)
This qualitative research was conducted to determine the benefits, reasons, experiences, knowledge of students in the development of writing instruments, students' understanding of descriptive paragraphs and Malay culture as local content in the classroom. This research is a survey research conducted in October 2020 and involved 50 respondents in grades VI, VII, IX of SMP Negeri 3 Kabun. To take the sample, the researcher used random sampling technique. The questionnaire is used as an instrument consisting of 17 questions which are then analyzed descriptively with an opinion that has been surveyed by researchers. To answer the researcher's question, the technique used is observation to analyze the completed questionnaire. The findings reveal that stationery is still used in modern times, students can also understand descriptive paragraphs. Students experience an increase in the value of writing descriptive paragraphs while some students are still unable to write descriptive paragraphs, students' understanding of using blog media is very good as a medium of learning and make students more interested so that it fosters motivation, teaching materials will be clearer and can be understood by students and allow students to master teaching objectives better, learning methods will be more varied, not boring students and students doing more learning activities. Riau Malay culture has not yet been applied to local content. If it is applied, it will make students understand the culture will increasingly develop among students.